2003
DOI: 10.1002/hbm.10110
|View full text |Cite
|
Sign up to set email alerts
|

The role of age of acquisition and language usage in early, high‐proficient bilinguals: An fMRI study during verbal fluency

Abstract: Abstract:We assessed the effects of age of acquisition and language exposure on the cerebral correlates of lexical retrieval in high-proficient, early-acquisition bilinguals. Functional MRI was used to study Spanish-Catalan bilinguals who acquired either Spanish or Catalan as a first language in the first years of life. Subjects were exposed to the second language at 3 years of age, and have used both languages in daily life since then. Subjects had a comparable level of proficiency in the comprehension of bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
244
1
14

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 387 publications
(279 citation statements)
references
References 54 publications
20
244
1
14
Order By: Relevance
“…While such changes in laterality have been reported, most neuroimaging evidence shows that non-identical neural sources in prefrontal cortex vary with language exposure or usage in early bilinguals (e.g., Perani et al, 2003) or vary in the extent of activation in Broca's area in late proficient bilinguals (Rüschemeyer, Fiebach, Kempe, & Friederici, 2005). In a recent paper Jeong and colleagues (2007) investigated the effect of syntactic similarity during L2 auditory language processing in Korean late trilinguals with equally high proficiency in their L2s (English and Japanese).…”
Section: The P600 and Phrase Structure Constraintsmentioning
confidence: 99%
“…While such changes in laterality have been reported, most neuroimaging evidence shows that non-identical neural sources in prefrontal cortex vary with language exposure or usage in early bilinguals (e.g., Perani et al, 2003) or vary in the extent of activation in Broca's area in late proficient bilinguals (Rüschemeyer, Fiebach, Kempe, & Friederici, 2005). In a recent paper Jeong and colleagues (2007) investigated the effect of syntactic similarity during L2 auditory language processing in Korean late trilinguals with equally high proficiency in their L2s (English and Japanese).…”
Section: The P600 and Phrase Structure Constraintsmentioning
confidence: 99%
“…First of all, a general delineation must clearly be drawn between L2 production and L2 comprehension studies. Although not all production studies focus on the same cerebral areas, the general conclusion drawn by the vast majority of this research has been that L1 and L2 are represented, at least to some degree, distinctly in the bilingual brain (Kim et al, 1997;Perani et al, 2003). It has been proposed, however, that such differences are related to difficulties in articulating a foreign language, rather than distinct representation of L1 and L2 per se (Klein et al, 1994(Klein et al, , 1995.…”
Section: Introductionmentioning
confidence: 96%
“…Evidence from the few available neuroimaging studies investigating bilingual reading has shown differences in regional activation profiles based on the L2 age-of-acquisition (AoA; Perani et al 2003;Wartenburger et al 2003), language proficiency (Meschyan and Hernández, 2006), and language orthography (Meschyan and Hernández, 2006;Das et al 2011;Jamal et al 2012). Overall, results from these studies revealed an extensive overlap in the language regions engaged for L1 and L2 reading in early, but not in late bilinguals (Wartenburger et al 2003).…”
Section: Introductionmentioning
confidence: 99%